1999
DOI: 10.1136/fn.80.3.f230
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of effect of nasal continuous positive pressure on laryngeal opening using fibre optic laryngoscopy

Abstract: Aim-To assess the eVect of nasal continuous positive airways pressure (CPAP) on the dimensions of the laryngeal opening. Methods-Nine preterm infants who had previously received ventilatory support for respiratory distress syndrome (RDS) were studied. All were receiving nasal CPAP. The laryngeal opening was visualised using a fibre optic video camera system. The ratio of width to length of the opening was measured on and oV CPAP. Results-In eight of the infants the width: length ratio increased on CPAP; mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Nasal CPAP has been previously reported to induce dilatation of laryngeal opening in preterm infants (9). On this basis, several neonatology teams are reluctant to initiate oral feeding in infants receiving nCPAP (23), probably fearing the cardiorespiratory consequences of triggering laryngeal chemoreflexes due to increased laryngeal penetration of milk.…”
Section: Safety Of Bottle-feeding During Ncpapmentioning
confidence: 99%
“…Nasal CPAP has been previously reported to induce dilatation of laryngeal opening in preterm infants (9). On this basis, several neonatology teams are reluctant to initiate oral feeding in infants receiving nCPAP (23), probably fearing the cardiorespiratory consequences of triggering laryngeal chemoreflexes due to increased laryngeal penetration of milk.…”
Section: Safety Of Bottle-feeding During Ncpapmentioning
confidence: 99%
“…The physiological effects of NCPAP include improved oxygenation2 3 and lung function,4 5 reduced upper airway resistance,6 7 stenting of the upper airway,8 preservation of lung volume9 and, at least with some devices, reduced work of breathing 10…”
mentioning
confidence: 99%
“…However, laryngeal functions, such as nonnutritive swallowing (NNS), which fulfils the important task of clearing upper airways from secretions and liquids refluxed from the stomach, have not been specifically assessed in newborns during nasal CPAP, aside from one study wherein nasal CPAP was shown to increase laryngeal opening (5). We recently reported that a nasal CPAP of 6 cmH 2 O inhibits spontaneous NNS in newborn lambs during quiet sleep (QS) (19).…”
mentioning
confidence: 99%